Evaluation of pharmaceutical assistance in municipalities in the state of Minas Gerais - Cristiano Soares de Moura; Edson Perini (Universidade de São Paulo, 2009)
The study proposal was to evaluate the pharmaceutical assistance in the state of Minas Gerais (MG) utilizing pharmaceutical assistance indicators described in the literature. The evaluated items were: organization, financing, selection, acquisition, programming, distribution, availability and storage of medicines in 18 municipalities of the Regional Management of Health of Belo Horizonte. The results have shown good performance respecting service organization, presence and updating of Municipal Essential Drug List. The main problems were related to stock control and availability of some items. The work has demonstrated the operational viability of indicators, as to evaluate the conditions of pharmaceutical assistance, as to monitor their performance. A proposta do estudo foi avaliar a assistência farmacêutica no estado de Minas Gerais (MG), utilizando indicadores da assistência farmacêutica descritos na literatura. Os itens avaliados foram: organização, financiamento, seleção, aquisição, programação, distribuição, disponibilidade e armazenamento de medicamentos em 18 municípios da Gerência Regional de Saúde de Belo Horizonte. Os resultados mostraram bom desempenho quanto à organização do serviço, presença e atualização da Relação Municipal de Medicamentos. Os principais problemas foram em relação ao controle de estoque e disponibilidade de alguns itens. O trabalho demonstrou a viabilidade operacional dos indicadores, tanto para avaliar as condições dos serviços farmacêuticos, quanto para monitorar seu desempenho.